Design of Plastic Waste Processing Extrusion Machines - Agus Haris Abadi; Ridwan Baharta; Masri Bin Ardin (Universitas Sultan Ageng Tirtayasa, 2024)
Plastic waste remains a significant unresolved issue due to extensive usage and lack of public awareness. It continues to be a problem in both rural and urban areas. The difficulty in eradicating plastic waste means that it will continue to accumulate if not addressed seriously. This study aims to develop equipment for processing plastic waste, including the main frame, component holder, heating tube, and screw extruder. This type of research falls under research and development (R&D) and involves the following steps: identifying potential and problems, gathering information, product design, design validation, and design improvement. The study findings are as follows: 1) The main frame is constructed using black hollow iron 30x30x1.6 mm; 2) Design drawings for the main frame, tube holder, heating tube, and screw extruder in both 2D and 3D formats are provided. These drawings include dimensions and work symbols in accordance with drawing rules; 3) The Von Mises Stress test on the main frame, conducted with a 100 kg load, indicates that the highest tension is located above the end of the middle support, with a value of 73.09 MPa. This value is far from the melting point. The part with the lowest stress is the lower frame, with a value of 0.02 MPa; and 4) The Von Mises Stress test on the tube holder, conducted with a 50 kg load, shows that the highest stress is at the bottom, with a value of 1.813 MPa. This value is far from the melting point. The part with the lowest stress is the lower seat of the side, with a value of 0.001 MPa.